2003
DOI: 10.1007/s11664-003-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on elastic properties of woven-glass epoxy composites for printed circuit board applications

Abstract: The effect of temperature on the elastic properties of woven-glass epoxy substrates for printed circuit board applications was investigated. Three common commercially pressed boards (1080, 2116, and 7628 woven-glass fabrics and FR4 epoxy) were used for this study. The elastic properties were identified by means of a combined theoretical and experimental vibration method. Vibration experiments were performed under reduced air pressure to reduce the influence of mass, stiffness, and damping of the surrounding ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…0.10 g pure bisphenol A was transferred to a 100 ml volumetric flask dissolved and make up to volume with anhydrous ethanol to get stock solution of 1000 lg/ml. Concentration of 5,10,15,20,25,30,35,40,45 and 50 lg/mL were prepared for making a standard curve (Fig. S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…0.10 g pure bisphenol A was transferred to a 100 ml volumetric flask dissolved and make up to volume with anhydrous ethanol to get stock solution of 1000 lg/ml. Concentration of 5,10,15,20,25,30,35,40,45 and 50 lg/mL were prepared for making a standard curve (Fig. S1).…”
Section: Methodsmentioning
confidence: 99%
“…conductive tracks laminated with fibreglass sheet, bonded with mixtures of polymer materials. Thermoset resin such as bromine epoxy resin (BER) is used as a flame retardant because PCBs are often exposed to high temperature both during manufacturing and operations [5]. BER are intermingled with metals [6] and glass fibres many times, which creates difficulty in individual components separation from WPCB and size reduction of WPCB for recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, present warpage prediction techniques use volume averaging to estimate these properties [3]. Nevertheless, studies by Hutapea and Grenestedt [8] show that the copper trace orientation has a noteworthy influence on the PCBs' warpage even when the board is completely copper balanced.…”
Section: Warpage Simulationmentioning
confidence: 99%
“…During the reflow soldering process, PCBs are exposed to temperatures ranging from 230°C to 250°C [2]. When subjected to temperature changes, the mismatch in the thermomechanical properties of the constituent materials of the PCBs leads to the appearance of significant thermal stresses [3,4]. Warpage is responsible for misalignments during the package assembly stage, smaller tolerances [4], imperfect soldering and consequent detachment of components [4].…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic elastic properties of this composite have been described by Hutapea and Grenestedt [55], shown in Table 4.2, while Shrotriya et al [56] characterized the viscoelastic properties, shown in Table 4.3.…”
Section: Viscoelastic Anisotropymentioning
confidence: 92%